Conditional HIF-1α expression produces a reversible cardiomyopathy - Bekeredjian, Raffi; Walton, Chad B.; MacCannell, Keith A.; Ecker, Jennifer; Kruse, Fred; Outten, Joel T.; Sutcliffe, David; Gerard, Robert D.; Bruick, Richard K.; Shohet, Ralph V. (PLOS ONE, 2010)
Background The response to hypoxia in tissues is regulated by the heterodimeric transcription factor Hypoxia Inducible Factor-1 (HIF-1). Methodology/Principal Findings We have created a strain of mice with inducible cardiomyocyte-specific expression of a mutated, oxygen-stable, form of HIF-1α. Cardiac function steadily decreased with transgene expression, but recovered after the transgene was turned off. Using long-oligo microarrays, we identified 162 transcripts more than 3-fold dysregulated in these hearts after transgene expression. Among the down-regulated genes the transcript for SERCA was reduced 46% and the protein 92%. This led us to an evaluation of calcium flux that showed diminished reuptake of cytoplasmic calcium in myocytes from these hearts, suggesting a mechanism for cardiac dysfunction. Conclusions/Significance These results provide a deeper understanding of transcriptional activity of HIF in the heart, and show that enhanced HIF-1 activity is sufficient to cause contractile dysfunction in the adult heart. HIF is stabilized in the myocardium of patients with ischemic cardiomyopathy, and our results suggest that HIF could be contributing directly to the contractile dysfunction in this disease.
Gesehen am 10.01.2023